1990
DOI: 10.1042/bj2710253
|View full text |Cite
|
Sign up to set email alerts
|

The effect of haem ligands on the redox states of the hexa-haem nitrite reductase from Wolinella succinogenes

Abstract: The nitrite reductase of Wolinella succinogenes containing six covalently bound haem groups has one haem group that will not reduce fully in the presence of excess Na2S2O4. The effect of the extrinsic ligands CO and cyanide on the redox state of this haem was studied by e.p.r. and magnetic c.d. spectroscopy. It was found that both ligands increased the extent of reduction of this haem group, and that in the case of CO binding the level of reduction was correlated with the extent of CO saturation of the enzyme.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The active-site heme is also surrounded by amino acid residues that are likely to be protonated, contributing to a positive electrostatic potential when nitrite binds (33). Strong cyanide binding to the reduced form of this type of enzyme from Wollinella succinogenes has been reported (34). We argue that the lysine in the heme binding motif is of crucial importance in promoting the binding of anions, and the environment of this heme contributes to the provision of a reduction potential low enough to reduce substrate nitrite through to ammonia.…”
Section: Discussionmentioning
confidence: 99%
“…The active-site heme is also surrounded by amino acid residues that are likely to be protonated, contributing to a positive electrostatic potential when nitrite binds (33). Strong cyanide binding to the reduced form of this type of enzyme from Wollinella succinogenes has been reported (34). We argue that the lysine in the heme binding motif is of crucial importance in promoting the binding of anions, and the environment of this heme contributes to the provision of a reduction potential low enough to reduce substrate nitrite through to ammonia.…”
Section: Discussionmentioning
confidence: 99%
“…In the resting form a marked band at 610 nm is seen in the enzyme's absorption spectrum, indicative of high-spin ferric haem, whereas the redoxcycled form is characterized by the presence of a broader ferric Soret band. There is no evidence that corresponding resting and redox-cycled forms of the enzyme exist in the reduced enzyme (Blackmore et al, 1990a).…”
Section: Introductionmentioning
confidence: 99%
“…The redox-cycled form also exhibits two kinetic steps, but, unlike the resting form, the rate of the slower of these steps shows a linear dithionite-concentration-dependence (Blackmore et al, 1990b). It has also been found that the low rate of dithionite reduction of resting nitrite reductase increased in the presence of cyanide, but the rate limit of this process was unchanged (Blackmore et al, 1990a). This can be accounted for if the reduction of the active-site ligand-binding haems is unfavourable owing to the low redox potential of the exchangecoupled haem pair.…”
Section: Introductionmentioning
confidence: 99%